Stopping Power of Electrons and Protons inPolyethylene TerephthalateC10H8O4, and PolyurethaneC17H16N2O4 - et. al., Noor Hilal Hadi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work ,the entireprotons stopping power has been calculated by using Ziegler formula. The protons’energy range were (10-2 keV to 103 keV). The entireelectrons stopping power with using Bethe-Blochformula was designed, the verve range of electrons as of 10 keV to 105 keV in PolyurethaneC17H16N2O4, and Polyethylene terephthalate C10H8O4which as a polymeric materials for manufacture the astronaut suit.The results in this research were compared with the values of the E-STAR program for light charged particles (electrons) and the values of the SRIM program for the heavy charged particles (protons), and they showed good compatibility and all the mentioned equations were programmed in MATLAB2013 language.